2020
DOI: 10.1007/s00228-020-02947-4
|View full text |Cite
|
Sign up to set email alerts
|

The added value of pirfenidone to fight inflammation and fibrotic state induced by SARS-CoV-2

Abstract: Aim SARS-CoV-2 infection has been divided by scientific opinion into three phases: the first as asymptomatic or slightly symptomatic and the second and the third with greater severity, characterized by a hyperinflammatory and fibrotic state, responsible for lung lesions, in some cases fatal. The development of antiviral drugs directed against SARS-CoV-2 and effective vaccines is progressing; meanwhile, the best pharmacological objective is related to the management of all the complications caused by this viral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 17 publications
(14 reference statements)
1
39
0
1
Order By: Relevance
“…SARS-CoV-2 uses the entry receptor ACE-2 to penetrate host cells (Li et al 2020a ; Vitiello and Ferrara 2020a , b ), the latter being expressed in several tissues, at the level of type II pneumocytes, cardiac cells, liver cholangiocytes, and endothelial cells. In the most severe stages of COVID-19 infection, a “cytokine cascade”(Vitiello et al 2020a ; Ferrara et al 2020a ) is generated, responsible for multi-system inflammation leading to organ injury (Ferrara et al 2020b ). As mentioned above, a percentage of COVID-19-infected patients show lesions of the cardiovascular system (Clerkin et al 2020 ; Vitiello and Ferrara 2020c ).…”
Section: Covid-19 Viral Infectionmentioning
confidence: 99%
“…SARS-CoV-2 uses the entry receptor ACE-2 to penetrate host cells (Li et al 2020a ; Vitiello and Ferrara 2020a , b ), the latter being expressed in several tissues, at the level of type II pneumocytes, cardiac cells, liver cholangiocytes, and endothelial cells. In the most severe stages of COVID-19 infection, a “cytokine cascade”(Vitiello et al 2020a ; Ferrara et al 2020a ) is generated, responsible for multi-system inflammation leading to organ injury (Ferrara et al 2020b ). As mentioned above, a percentage of COVID-19-infected patients show lesions of the cardiovascular system (Clerkin et al 2020 ; Vitiello and Ferrara 2020c ).…”
Section: Covid-19 Viral Infectionmentioning
confidence: 99%
“…Pulmonary fibrosis may be responsible for severe lung injury from COVID-19. 7 Some evidence associates pulmonary antifibrotic effects to statins. 8 Some studies have shown an increase in ACE-2 expression following treatment with statins.…”
mentioning
confidence: 99%
“…[ [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] ].…”
Section: Uncited Referencesunclassified